Analysis of risk factors for antiepileptic drug-induced adverse psychotropic effects in Chinese outpatients with epilepsy. (May 2019) - Du, Yan-ru; Lin, Jia-he; Mei, Pei-na; Wang, Li; Wang, Yi; Shen, Jing-zan; Ding, Si-qi; Ye, Meng-qian; Wang, Xin-shi; Xia, Nian-ge; Zheng, Rong-yuan; Chen, Hong; et al.
Highlights: Of all APEs, the effects on memory and sleep are most pronounced. Female, psychotic comorbidities, AEDs polytherapy and the duration of epilepsy are nondrug risk factors for APEs. Clinicians should pay close attention to APEs and choose drugs carefully. Abstract: Antiepileptic drugs (AEDs) have adverse psychotropic effects (APEs). To explore the risk factors for AED-induced APEs, we compared Chinese outpatients with epilepsy with and without AED-induced APEs. We reviewed the medical data of outpatients with epilepsy enrolled in the Epilepsy Long-term Follow Up Registry Study (ELFURS) between January 1, 2003 and December 31, 2015. Data on demographics, comorbidities, variables related to epilepsy, AED use, and APEs were collected. APEs were determined by experienced epileptologists based on the definition of "adverse drug reaction (ADR)" proposed by the World Health Organization (WHO) in 1972, and the causality relationship between APEs and suspected medications was assessed based on the WHO-UMC scale. APEs included effects on memory, sleep, behavior, mood, psychotic symptoms, and others in this study. We divided the study population into patients with and without AED-induced APEs and then compared the differences between the two groups using univariate and multivariate methods. A total of 3074 eligible patients were included in this study (1001 patients with AED-induced APEs and 2073 patients without AED-induced APEs). Of all APEs, the effects on memory and sleep were most pronounced. The results show that the female sex (odds ratio [OR] 1.242, 95% confidence interval [CI] 1.055–1.463), psychotic disorder comorbidities (OR 1.815, 95% CI 1.159–2.841), polytherapy with AEDs (OR 1.400, 95% CI 1.061–1.847), and the duration of epilepsy (OR 1.010, 95% CI 1.000–1.020) are significant nondrug risk factors for AED-induced APEs. Recognizing risk factors for APEs may help determine optimal treatment strategies for epilepsy.